Pertimbangan Hukum Dalam Mengabulkan Perkara Isbat Nikah Contensius Di Pengadilan Agama Sangatta - Nur Sholfa Adilla; Hartono Hartono; Mukhtar Mukhtar (CV. ITTC INDONESIA, 2025)
Many people conduct religious or customary marriages without registering their marriages at the Office of Religious Affairs (KUA) or civil registration institutions. As a result, the legal status of their marriage becomes unclear, which in turn has an impact on the non-recognition of legal rights, such as inheritance rights, maintenance rights, and the validity of the status of children. This study aims to analyze the legal considerations and factors influencing judges' decisions in isbat contensius cases. This research uses a qualitative method with a juridical-sociological approach, where data is collected through interviews, observation, and documentation studies. The results showed that the legal considerations used by judges in granting contensius isbat nikah cases at the Sangatta Religious Court were based on Law Number 1 of 1974 concerning Marriage, especially Article 2 Paragraph 2, as well as Article 7 Paragraph 3 of the Compilation of Islamic Law (KHI) which regulates the reasons for applying for isbat nikah.